THE PROBLEM OF SHARI'AH BANKS IN APPLYING ISLAMIC LAW - Firdaus Firdaus (Jurnal Kajian dan Pengembangan Umat, 2019)
Syari'ah Bank was established to be an alternative for Muslims who consider bank interest to be illegitimate with a variety of products. The concept of image and position of Islamic banks is more than just a bank that runs the principles of justice, honesty, transparency, and is free from usury, gharar (fraud), maysir (speculation), and other things that are not in accordance with sharia. However, why is the pace of Islamic banks stagnant. Islamic banks do not seem to work as they should, which still smell of usury, gambling and injustice and extortion. It is hoped that the supervisory role of Islamic banks can be increased and there is a renewal of the system so that Islamic banks can be released from usury, gambling and actions that violate other Shari'a. Islamic banks should be able to carry out their activities in the real sector so that they can also help these Islamic banks regardless of the things that are prohibited by syara '.